PEMBUATAN SERBUK U-6Zr DENGAN PENGKAYAAN URANIUM 19,75 % UNTUK BAHAN BAKAR REAKTOR RISET - Masrukan Masrukan; Sungkono Sungkono; Yanlinastuti Yanlinastuti; Tri Yulianto; Ridwan Ridwan (website, 2015)
ABSTRAKPEMBUATAN SERBUK PADUAN U-6Zr DENGAN PENGKAYAAN URANIUM 19,75 % UNTUK BAHAN BAKAR REAKTOR RISET. Telah dilakukan pembuatan serbuk paduan U-6Zr dengan pengkayaan 19,75 % untuk bahan bakar reaktor riset. Pembuatan bahan bakar U-6Zr ini dalam rangka mencari bahan bakar baru yang mempunyai densitas tinggi untuk mengganti bahan bakar yang sudah ada U3Si2-Al. Tujuan dari percobaan ini untuk mengetahui sifat-sifat serbuk paduan U- 6Zr yang diperoleh dari proses hydriding-dehydriding sebagai kandidat bahan bakar reaktor riset. Serbuk yang diperoleh dari proses hydriding-dehydriding dikenai pengujian, diantaranya pungujian komposisi kimia, densitas, kandungan hidrogen, fasa dan sifat termal. Hasil pengujian komposisi kimia menunjukkan beberapa unsur seperti Al, Ca, Cu, dan Ni melebihi batas yang diijinkan dimana masing-masing unsur terdapat sebesar 202,21 ppm; 214,05 ppm; 61,25 ppm dan 134,53 ppm. Pada pengujian diperolah densitas serbuk U-6Zr sebesar 13,58 g/cm3 dan pada pengujian kandungan hidrogen sisa diperoleh kandungan hidrogen sebesar 0,16 %. Untuk pengujian fasa, diperoleh fasa αU dan δU, sedangkan pada pengujian sifat termal yakni transformasi temperatur terdapat dua puncak yakni puncak pertama terjadi pada temperatur 274 hingga 311 oC dan puncak kedua terjadi pada temperatur 493 hingga 527oC. Puncak pertama terjadi reaksi endotermik dengan menyerap panas sebesar ∆H = 6,23 cal/g tetapi tidak terbentuk fasa baru, sedangkan puncak kedua terjadi reaksi eksotermik dengan mengeluarkan panas sebesar ∆H = -9.34 cal/g dan terbentuk fasa αZr. Sementara itu, dari pengujian kapasitas panas pada temperatur 34 hingga 75 oC, terjadinya penurunan nilai kapasitas panas yang disertai dengan penyerapan panas. Pada temperatur yang lebih tinggi hingga temperatur 437oC nilai kapasitas panas menjadi lebih kecil disertai pengeluaran panas. Reaksi termokimia antara Zr dengan hidrogen sisa menunjukkan terbentuknya fasa αZr yang diindikasikan oleh reaksi eksotermik dengan mengeluarkan panas sebesar ∆H = 9,3449 cal/g. Dari hasil analisis dapat diketahui bahwa paduan U-6Zr tersebut dapat digunakan sebagai bahan bakar pengganti untuk reaktor riset. Kata kunci: Serbuk U-6Zr, pengkayaan U 19,75 %, bahan bakar, reaktor riset. ABSTRACTMAKING OF U-6Zr ALLOY POWDER WITH URANIUM ENRICHMENT OF 19.75 % FOR RESEARCH REACTOR FUEL. Making U-6Zr alloy powder with enrichment of 19.75 % for a research reactor fuel has been done. Making of U-6Zr fuel in order to find new fuels that have a high density to replace the existing fuel U3Si2-Al. The purpose of this experiment was to determine the properties of U-6Zr alloy powder obtained from the hydriding-dehydriding process as a candidate research reactor fuel. Initially was made U-6Zr ingot by melting U and Zr metals using electric arc melting furnace. U-6Zr ingots were found then cut into pieces and put into hydriding-dehydriding equipment that operates at pressures 14,46054 psi and hydriding temperatures of 350 oC. Ingots that out of the hydriding-dehydriding equipment becomes brittle then was crushed so becomes powder. Powder that obtained subjected to the test, including chemical composition testing, density, hydrogen content, phase and thermal properties. The results testing show that chemical composition of some elements such as Al, Ca, Cu, and Ni exceeded the permitted limit, each of which contained elements of 202.21 ppm, 214.05 ppm, 61.25 ppm, and 134.53 ppm. On testing the density obtained that U-6Zr powder density of 13.57 g/cc and the testing of hydrogen residual content obtained hydrogen residual content of 0.16 %. For the testing phase were obtained the αU and δU phases, while in testing of the transformation temperature, there are two peaks, the first peak occurs at a temperature of 274 to 311 °C and a second peak occurs at a temperature of 493 to 527 oC. The first peak occurs endothermic reaction by absorbing heat of 6.23 cal/g but not formed a new phase, while the second peak occurs exotermic reaction with brought out heat of -9.34 cal/g and formed αZr phase. Meanwhile, the heat capacity of the test at temperature of 34 to 75 °C, the decrease in the value of the heat capacity accompanied heat absorption. At higher temperatures up to 437 °C, heat capacity value becomes negative and accompanied by heat expenditure. It can be concluded that the alloy the U-6Zr when viewed from the chemical composition can still be used for fuel research reactor. Residual hydrogen still found in small quantities in the U-6Zr powder that can be eliminated by heating for longer. Reaction between Zr with residual hydrogen to form the αZ phase is accompanied exothermic reaction with brought out heat of 93 449 cal/g.Keywords: U-6Zr powder, U enrichment of 19.75 %, fuel, research reactor.